Numerical study of magneto-hydrodynamic (MHD) mixed convection flow in a lid-driven triangular cavity - Uddin, Mohammed Nasir; Farhana, Aki; Alim, Md. Abdul (Journal of Naval Architecture and Marine Engineering, 2015)
In the present paper, the effect of magneto-hydrodynamic (MHD) on mixed convection flow within a lid-driven triangular cavity has been numerically investigated. The bottom wall of the cavity is considered as heated. Besides, the left and the inclined wall of the triangular cavity are assumed to be cool and adiabatic. The cooled wall of the cavity is moving up in the vertical direction. The developed mathematical model is governed by the coupled equations of continuity, momentum and energy to determine the fluid flow and heat transfer characteristics in the cavity as a function of Rayleigh number, Hartmann number and the cavity aspect ratio. The present numerical procedure adopted in this investigation yields consistent performance over a wide range of parameters Rayleigh number Ra (103-104), Prandtl number Pr (0.7 - 3) and Hartmann number Ha (5 - 50). The numerical results are presented in terms of stream functions, temperature profile and Nussult numbers. It is found that the streamlines, isotherms, average Nusselt number, average fluid bulk temperature and dimensionless temperature in the cavity strongly depend on the Rayleigh number, Hartmann number and Prandtl number.